DETERMINANTS OF FIRM PERFORMANCE DURING FINANCIAL CRISIS PERIOD: A CASE OF TURKISH FINANCIAL CRISIS IN 2001 - Demirci, Ebru (2011)
This paper studies the determinants of the firm performance during the currency crisis in Turkey in 2001. The empirical model consists of firm specific determinants and the analysis of the model is done in two stages. At first stage all the determinants are analysed in an industry free model. As second stage the same model is grouped and analysed according to industries. The results suggest that size, ownership structure and export/sales ratio of the firm affects the stock return negatively whereas maturity, debt exposure and ROE contributes positively. Furthermore industry specific differences within these determinants are observed. Each of the determinants is found to perform different ways of interaction with the stock returns when industries are included in the model.